Towards the activation of the environmental tax incentives to reduce the environmental pollution risks in Algeria - dahdouh, nabil; benaichouba, rafika (Journal of Research in Finance and Accounting, 2022)
This study aims to clarify the role of the activation of the environmental tax incentives in reducing the risks of environmental pollution in Algeria. The study addressed the conceptual framework of environmental pollution and environmental taxation. Environmental tax incentives, their tools, and the structure of Algeria's environmental taxes and fees were also identified. The results emphasize the importance of embodying the activation of fiscal incentives as a mechanism to reduce the environmental pollution risks in Algeria. Results also show that deterrent taxes and fees are ineffective and inefficient, resulting in companies' failure to reduce pollution concerns.